Genetic screens reveal CCDC115 as a modulator of erythroid iron and heme trafficking. Issue 9 (9th July 2020) - Sobh, Amin; Loguinov, Alex; Zhou, Jie; Jenkitkasemwong, Supak; Zeidan, Rola; El Ahmadie, Nader; Tagmount, Abderrahmane; Knutson, Mitchell; Fraenkel, Paula G.; Vulpe, Christopher D.
Abstract: Transferrin‐bound iron (TBI), the physiological circulating iron form, is acquired by cells through the transferrin receptor (TfR1) by endocytosis. In erythroid cells, most of the acquired iron is incorporated into heme in the mitochondria. Cellular trafficking of heme is indispensable for erythropoiesis and many other essential biological processes. Comprehensive elucidation of molecular pathways governing and regulating cellular iron acquisition and heme trafficking is required to better understand physiological and pathological processes affecting erythropoiesis. Here, we report the first genome‐wide clustered regularly interspaced short palindromic repeats (CRISPR) screens in human erythroid cells to identify determinants of iron and heme uptake, as well as heme‐mediated erythroid differentiation. We identified several candidate modulators of TBI acquisition including TfR1, indicating that our approach effectively revealed players mechanistically relevant to the process. Interestingly, components of the endocytic pathway were also revealed as potential determinants of transferrin acquisition. We deciphered a role for the vacuolar‐type H+ − ATPase (V‐ ATPase) assembly factor coiled‐coil domain containing 115 (CCDC115) in TBI uptake and validated this role in CCDC115 deficient K562 cells. Our screen in hemin‐treated cells revealed perturbations leading to cellular adaptation to heme, including those corresponding to trafficking mechanisms and transcription factors potentiating erythroid differentiation. Pathway analysis indicated that endocytosis and vesicle acidification are key processes for heme trafficking in erythroid precursors. Furthermore, we provided evidence that CCDC115, which we identified as required for TBI uptake, is also involved in cellular heme distribution. This work demonstrates a previously unappreciated common intersection in trafficking of transferrin iron and heme in the endocytic pathway of erythroid cells.